Reduced body sizes in climate-impacted Borneo moth assemblages are primarily explained by range shifts - Chung-Huey Wu (Nature Portfolio, 2019)
Body size shifts under climate change may arise from species range shifts, intraspecific size shifts, or both. Here the authors show that body size reduction in moth assemblages on Mt. Kinabalu, Borneo, over 42 years are driven more by species range shifts than by within-species shrinkage.